Pengaruh Work Life Balance Dan Burnout Terhadap Sustainable Performance Pada PT Surteckariya Indonesia - Aslim Hanifah; Aprilia Puspasari (Journal of Innovative and Creativity (Joecy), 2026)
This study aims to analyze the effect of Work Life Balance and Burnout on Sustainable Performance among employees of PT Surteckariya Indonesia. Sustainable Performance refers to employees' ability to maintain optimal, productive, consistent, and sustainable performance over the long term without compromising their physical and mental well-being. This research employed a quantitative method with an associative approach to examine the relationship between Work Life Balance, Burnout, and Sustainable Performance. The population consisted of 598 employees of PT Surteckariya Indonesia, with a sample of 376 respondents selected using the simple random sampling technique. Data were collected through questionnaires using a Likert scale and analyzed using SPSS version 26. The data analysis techniques included validity testing, reliability testing, classical assumption tests, multiple linear regression analysis, partial testing (t-test), simultaneous testing (F-test), and coefficient of determination analysis. The results indicate that Work Life Balance has a positive and significant effect on Sustainable Performance, while Burnout has a positif and significant effect on Sustainable Performance. Furthermore, Work Life Balance and Burnout simultaneously have a significant effect on Sustainable Performance. These findings suggest that a better balance between employees’ work and personal lives enhances their ability to maintain sustainable performance. Conversely, higher levels of burnout reduce employees’ ability to sustain productivity, work quality, and long-term performance. Therefore, organizations should create a supportive work environment that promotes work-life balance and implement effective strategies to reduce burnout in order to improve employees’ sustainable performance.